Success drivers of sports crowdfunding campaigns - Brochado, A. (2018)
Crowdfunding combines social networking with microfinance in a method of financing new ventures that has become increasingly popular. Crowdfunding offers entrepreneurs an opportunity to find a large number of investors for projects, but many campaigns tend to remain unfunded. This study’s main objective was to access the main success drivers of crowdfunded projects, focusing, in particular, on sports projects. The dataset comprised 4,952 donationand rewards-based projects launched in three platforms. Two models were estimated to explain both the success over failure rate and overfunding of crowdfunding projects in terms of specific campaign characteristics. The results reveal that higher project funding goals are correlated with a lower probability of success and overfunding, while successful projects are associated with a higher number of backers and flexible funding. Donation-based projects appear to increase the likelihood of success compared with reward-based projects.